Current perspectives on performance improvement in the marathon: from universalisation to training optimisation - Billat, V. (New Studies in Athletics, 2005)
The marathon is the event setting the golden standard in human endurance at a speed of 20 km.h-1. Since 1984, the marathon performance has been improved by 6min (4%) in females (2:21:06 vs. 2:15:25) and by 3 minutes (2%) (2:07:12 vs. 2:04:55) in males. Furthermore, the Marathon is one of the rare sports in which elite and non elite compete together. In the last two decades, almost 500,000 runs have been performed in the London Marathon over the last 20 years and the same in New York and Paris ones. Indeed, in year 2000, over 35,000 people run the Paris. The aim of this paper is to highlight the possible cause of the marathon performance improvement: 1°) the universalization of the Marathon running in more and more country, especially in women; 2°) an optimization of training to enhance the energetical factors of performance on marathon and at last, 3°) an improvement of physiological strain during a marathon thank to new technologies in order to improve the specificity of training.